Contribution of Professional Competence and Supervision Toward Vocational High School Teachers’ Performance in Lima Puluh Kota District - Rabi’atul Awaliyah; Rusdinal Rusdinal; Yahya Yahya (Postgraduate School, Universitas Negeri Padang, 2019)
The research objectives were to assess: 1) How big the contribution of professional competence toward the teachers' performance was. 2) How big the contribution of the implementation of the supervision toward the teacher's performance was. 3) How big the contribution of professional competence and the jointly supervised implementation toward the teachers’ performance in Lima Puluh Kota District was. The type of this research is correlational quantitative research design. This research was conducted at the existing Vocational High Schools in Lima Puluh Kota District (henceforth: VHS in LPK District), on all civil servant teachers at the schools during 2011/2012 school year. The study population was all the teachers of the schools that were actively teaching from July to December 2011 with the total of 97 people. The collection of samples in this study used stratified random sampling technique. The data were collected at VHS in LPK District done by directly seeing the respondents during office hours at the teacher's room. The data were analyzed using statistical techniques of correlation and regression used to test the hypothesis. Based on the results of analysis, professional competence contributed to the teachers’ performance with the number of 41.6%. This means that the professional competence contributed to teachers’ performance. The implementation of supervision contributed the teachers’ performance with the number of 12.9%. Since the implementation of the Supervision contributed significantly to teachers’ performance, it means that the higher the implementation of supervision is, the better the performance of teachers in performing their duties will be. In conclusion, the professional competence and the implementation of Supervision jointly contributed to the teachers’ performance of 47.3%. This means that in order to improve teachers’ performance, there should be an effort to increase the profesional competence and the good implementation of supervision by supervisors or head masters.